2021
DOI: 10.1371/journal.pone.0254104
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type TTR amyloidosis among patients with unexplained heart failure and systolic LV dysfunction

Abstract: Aim Transthyretin cardiac amyloidosis (ATTR-CA) is an increasingly recognized cause of heart failure (HF) with preserved left ventricular ejection fraction (LVEF), typically presenting as restrictive cardiomyopathy. The potential co-existence of ATTR-CA with systolic heart failure has not been studied. The aim of this study is to describe the prevalence of ATTR-CA and its clinical characteristics in HF patients with reduced LVEF. Methods Patients with an unexplained cause of LV systolic dysfunction were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…is provided in Table 1 8–25,34–77 . A graphical representation of the prevalence of cardiac amyloidosis across various populations subgroups is provided in Figure (and online supplementary Figure – focused version).…”
Section: Resultsmentioning
confidence: 99%
“…is provided in Table 1 8–25,34–77 . A graphical representation of the prevalence of cardiac amyloidosis across various populations subgroups is provided in Figure (and online supplementary Figure – focused version).…”
Section: Resultsmentioning
confidence: 99%
“…Specific clinical settings have been recognized as strongly associated with CA but further studies are needed to better characterize these populations, mainly to stratify patient risk and evaluate which patients are ideal candidates for the newly available disease-modifying therapies. Acknowledgments: We would like to thank all the nuclear medicine doctors, hematologists, neurologists, pathologists and nephrologists of the participating centres for providing their essential [8,[13][14][15][16]20,27,28,33,[36][37][38][39]41,42,[46][47][48][49][50][51][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of ATTR-CA was also evaluated in patients with HFrEF/HFmrEF; Lopez-Sainz et al reported a prevalence of approximately 11% in HFrEF/HFmrEF patients [ 41 ], while Goland et al found ATTR-CA in 9.3% of 75 HF patients with reduced LVEF [ 42 ] ( Table 1 ).…”
Section: Prevalence Of Ca In Different At-risk Scenariosmentioning
confidence: 99%
See 2 more Smart Citations